2021
DOI: 10.1002/rcm.9201
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of equine liver microsome‐generated metabolites of growth hormone secretagogue small molecule ibutamoren

Abstract: Interest in growth hormone secretagogues has intensified during the past several years based on capable, ever-widening investigational applications of recombinant growth hormone in animals and humans. Ibutamoren is a potent, long-acting, selective and orally active non-peptide growth hormone secretagogue, which has a great potential for abuse as a performance-enhancing agent in sports.Methods: To support drug metabolism and pharmacokinetic studies of chiral pharmaceuticals, it is necessary to combine the resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(39 citation statements)
references
References 16 publications
12
27
0
Order By: Relevance
“…All the metabolites detected in this study were reported in the previously published in vitro work 21 ; structural interpretations of these analytes were consistent with what is reported in the current study. However, some additional oxygenated metabolites were also detected in that study, 21 including an additional metabolite mono‐oxygenated at the piperidine ring, a metabolite di‐oxygenated at the piperidine ring and a metabolite di‐oxygenated at the benzyl ring. Furthermore, five tri‐oxygenated metabolites were detected that were not observed in this study.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…All the metabolites detected in this study were reported in the previously published in vitro work 21 ; structural interpretations of these analytes were consistent with what is reported in the current study. However, some additional oxygenated metabolites were also detected in that study, 21 including an additional metabolite mono‐oxygenated at the piperidine ring, a metabolite di‐oxygenated at the piperidine ring and a metabolite di‐oxygenated at the benzyl ring. Furthermore, five tri‐oxygenated metabolites were detected that were not observed in this study.…”
Section: Resultssupporting
confidence: 92%
“…Figure 1 shows the acquired MS/MS spectrum and the proposed identities of the observed fragment ions. The fragmentation of MK‐0677 using positive ESI‐MS/MS has previously been reported, 17,21 and the major ions are consistent with what was observed in this study. The base peak ion was observed at theoretical m/z 91.0542, representing the benzyl moiety.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations